Enormity and Effects of Playing Online Video Games with a Violent Content amongst Adolescents - Muzna Mehmood, Noor- ul-ain Awan, Khawar Batool, Muzna Mehmood, Noor- ul-ain Awan, Khawar Batool (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Video gaming is an evolving problem that many of the parents are facing but more importantly, it is affecting the young generation through its physical and mental consequences. Methods: In this cross-sectional study, 75 teenagers were selected via random stratified sampling. Each participant was required to complete a survey that gathered data about their habits, attitudes, school performance and traits like hostility, empathy etc. on a 5-point Likert scale (1= ‘‘no violence’’ to 5= ‘‘extremely violent’’). Video games included any games played on computer, video game consoles hand-held game devices or in video arcades. Results: Out of a sample of 75 teens, 9 (12.0%) played non-violent or slightly violent games while 66 (88.0%) played violent games. Similarly, when the preferences of boys regarding the violent games were inquired, 6 (8%) boys preferred non-violent or slightly violent games while 69 (92%) preferred to play violent games. Conclusion: Majority of adolescent boys prefer to play video games with violent contents. The duration of time spent on playing video games in holidays and weekends is exceedingly higher in boys who prefer to play violent games. The violence in video games was shown to be affecting the habits, attitudes and daily life of children. Parental preferences and academics were not found to be related to the individual preferences of children.